PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PARA BURUH DI KABUPATEN BEKASI: (STUDI KASUS KEPEGAWAIAN DI KABUPATEN BEKASI, CIKARANG, PROVINSI JAWA BARAT) - Muhammad Wardiman; Muhammad Naufal Fahrezi; Renaldi Adi Baskoro; Syaiful Arifin Wahid; Adzan Purnama (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This research aims to analyze the influence of leadership style on the work motivation of workers in Bekasi Regency. The research method used is a case study by collecting data through questionnaires distributed to respondents who are workers in various industrial sectors in Bekasi Regency. The independent variable in this research is leadership style, while the dependent variable is work motivation. The collected data was analyzed using regression techniques to identify the relationship between leadership style and the level of work motivation. The research results show that leadership style has a significant influence on the work motivation of workers in Bekasi Regency. A leadership style that is supportive, inspiring and provides clear direction has been proven to be able to increase the level of work motivation of workers. In addition, factors such as effective communication, recognition of work contributions, and building good interpersonal relationships also contribute to high work motivation. This research provides an important contribution to the development of human resource management in the industrial sector of Bekasi Regency. The practical implications of these findings can help companies to better understand the important role of leadership style in increasing workers' work motivation, so that they can implement more effective and sustainable management strategies. In addition, this research also provides a basis for further research on the factors that influence job performance and satisfaction in the wider industrial sector.